A study on employee retention at Fuji Electric (M) Sdn. Bhd., Kulim Hi Tech Park / Syaridah Nazirah Saidin - Saidin, Syaridah Nazirah (2011)
The project paper title “A Study on Employee Retention at Fuji Electric (M) Sdn Bhd, Kulim Hi Tech Park” is conducted as partial requirement as needed by Faculty of Business Management, University Technology Mara (UiTM). The purpose of the study is to identify the relationship between gender and employee retention, to determine the most factors influencing employee retention and to examine significant relationship between the factors influence employee retention at Fuji Electric (M) Sdn. Bhd, Kulim Hi Tech Park. The analysis was found that, male employee more to stay for long period in Fuji Electric compared to female employee. Besides, further analysis was revealed that, most employee from the technician level chooses to stay in Fuji Electric because of they satisfy with their company’s work environment. Satisfaction employee with company’s environment make work environment become the most factors influencing employee retention at Fuji Electric (M) Sdn. Bhd. In addition, by analyzing using Pearson’s Correlation method there also have significant relationship with work environment, training and development, and leadership except reward and communication shows weak significant relationship with correlation coefficient only 0.464 and 0.420 which close to 0.